Photodynamic action of sulphonated aluminium phthalocyanine (SALPC) on AR4-2J cells, a carcinoma cell line of rat exocrine pancreas. - Matthews, E. K. (1990)
The photodynamic effects of sulphonated aluminium phthalocyanine (SALPC) have been compared on cultured AR4-2J cells of a pancreatic carcinoma cell line and on exocrine cells of the normal phenotype freshly isolated from the rat pancreas; a multi-channel perifusion system was used for this kinetic study in vitro. Whereas light alone or SALPC alone was without effect on either cell type, photon activation of cellularly-bound SALPC with light greater than 570 nm permeabilised the cells and caused an increase in amylase secretion from normal acinar cells but a dose-dependent inhibition (10(-7) to 10(-5) M) of amylase release from AR4-2J cells. In contrast, direct permeabilisation of the plasma membrane with digitonin, 10 micrograms ml-1, evoked a marked release of amylase from both types of cell. Elevation of [Ca2+]i by the ionophore A23187, 10(-6) M, elicited secretion of amylase from normal cells but had little effect on AR4-2J cells. Finally, it was established that the differential photodynamic effects of SALPC on amylase release were not attributable to any topographical differences in the microanatomical organisation of normal or tumour-derived cells; furthermore, the structural integrity of normal and AR4-2J cells was maintained after the photodynamic action of SALPC. It is concluded that the generation of singlet oxygen is responsible for permeabilisation of both types of cell and that photon-activated SALPC has functionally distinct effects on the constitutive secretion of amylase of tumour cells and the regulated secretory pathway of normal cells. These observations may be important in the development of drugs with a selective photodynamic action on pancreatic tumour cells.